CENTRAL ASIA BETWEEN WEST AND EAST - SPECHLER, Martin C. (CENTRAL ASIA AND THE CAUCASUS, 2005)
When I was first asked to speak about the prospects of EU expansion into Central Asia, I replied that this would be a very short paper! There is no such prospect. But no one with my love for speaking would let it go at that. So, I decided to interpret the question in a different way: would it be preferable for some or all of the Central Asian countries to seek some kind of associate status with the West or with the East, or with neither, nor with both—through the World Trade Organization? And would they be accept-ed by the EU, ASEAN, or the WTO? Would closer ties with Russia or China be a good idea? In this essay these possibilities are considered in turn. Let’s start with a few definitions and basic facts. I define the Central Asian (CA) states as the former Soviet republics of Azerbaijan, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. The first is to the west of the Caspian Sea, but its culture and political-economic regime are similar to the others. The Xinjiang-Uighur Autonomous Region of the People’s Republic of China, Afghanistan, the Azeri parts of Iran, and several Turkic1 parts of the Russian Federation might likewise be included as Central Asian, but except for Afghanistan, none of these areas is a sovereign entity able to arrange its own trade affairs. Since the Treaty on European Union specifies that membership is open to “European” states, the implication is that these clearly Asian states are not even remotely candidates for membership in the EU.2All these six Turkestani states of Central Asia are landlocked, remote from the main world markets. Azerbaijan has just been connected to the Mediterranean by the Baku-Tbilisi-Ceyhan oil pipeline, and Turkmenistan and Kazakhstan have gas or oil connections to Russia, but these are limited in capacity. All six states are ruled by authoritarian presidents who hold to an ideology of secular nationalism as opposed to political Islam.one is a “democratic” state. Human rights, free media, and an independent judiciary are all missing. Not one has held a fair election, in the estimation of OSCE or other outsider observers. All suffer from corruption and weak protection of private property, especially the petroleum-rich states among them. Hence, even aside from geography, they do not presently meet the Copenhagen criteria for membership in the European Union.Within a basically authoritarian political regime, all of these regimes have pursued some gradual economic reforms, with an external strategy I call “export globalism”—dependence on staple exports with multilateralism as contrasted with regional integration or neocolonialism. Except for the capital or main commercial cities, they are poor, even if high energy prices lately appear to put Kazakhstan, Azerbaijan, and possibly Turkmenistan into a slightly higher GNI category. Owing to Soviet-era development of their health and educational facilities, their U.N. (UNDP)human development indices are rated “medium. "The poorest sections of Uzbekistan (Karakalpakstan, near the devasted Aral Sea), parts of Kazakhstan, and the mountainous regions of Tajikistan and Kyrgyzstan have lost significant population, as many males have left for Russia or elsewhere to earn money in manual labor. Skilled Germans, Slavs, and Jews had departed in the 1990s.